Agricultural Policy: Systematic Literature Review - Nasution, Faiz Albar; Fahreza, Imam; Thamrin, Muhammad Husni (Talenta Publisher, 2023)
In general, agriculture is a neutral sector in a country. In this case, many countries rely on the agricultural sector, where agriculture is the primary production in economic development, often referred to as agrarian countries. The main objective of agricultural policy is to maintain agricultural production by achieving economic benefits compatible with poverty reduction as a final reaction to meet the population's social needs with the least possible impact. Seeing the problems and opportunities in the agricultural sector that also have socio-political impacts, this research is vital to understanding the implications and implementation of agricultural policies. This research uses a bibliometric analysis method to see the research development with the keyword